Relationship between room characteristics and speech intelligibility in contemporary churches in Malaysia - Din, N.C.; Lew, H.Y.; Razak, A.S.A. (Universiti Malaysia Pahang, 2016)
Church as a place of worship has a unique architectural style and is of great social importance for the Christian community. The church geometric configurations vary from classical cruciform to octagonal-shaped plan. Acoustically, some geometric shapes work much better than others while others can be downright awful. The objective of this study is to investigate the relationship between room characteristics and speech intelligibility in church acoustics. At the first stage of this study, a total of eight existing churches in Malaysia were identified and then grouped into three types, i.e. fan, rectangular, and cruciform. Then, a fan-shaped room model was selected to be simulated in detail for sectional studies. Nine different ceiling shapes were constructed for evaluation purposes. All the selected churches were modelled using the 3D modelling software, SketchUp and then exported into the commercial acoustic software, ODEON, for acoustical simulation. The simulated results were then compared to the parameter of speech transmission index (STI). The results indicate that there was no specific relationship of the STI with all three groups of room types. However, a direct relationship between the STI means value with its room volume as well as its distance between sound source and receiver points can be observed, whereby F3 being the highest average value of STI (0.44) whereas R2 showed the lowest average value of STI (0.30). All room models generally achieved 'fair' STI values at the front position of the altar but the STI values drop into 'poor' when the distance exceeds over than 6.5 m. In the second stage, the results obtained show a direct relationship between the STI means values with the lower ceiling height above the sound source and a shorter distance between the sound source and its surrounding walls that may provide higher speech intelligibility due to the strong early sound energy. This paper provides fundamental data on the relationships between room characteristics and speech intelligibility, which would then help with future refinements.